2000
DOI: 10.1046/j.1464-410x.2000.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of terazosin and tamsulosin for symptomatic benign prostatic hyperplasia in Japanese patients

Abstract: Objective To compare the ef®cacy and safety of an incremental-dose regimen of terazosin (1±2 mg daily) and a ®xed-dose regimen of tamsulosin (0.2 mg daily), on Japanese patients with symptomatic benign prostatic hyperplasia (BPH). Patients and methods This multicentre, single-blind, randomized trial compared terazosin and tamsulosin over 4 weeks, in 61 patients with symptomatic BPH randomly assigned to terazosin (n=31) or tamsulosin (n=30). Terazosin 0.5 mg twice daily was administered for 2 weeks, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 20 publications
3
41
0
Order By: Relevance
“…In Asia, the appropriate dose of tamsulosin has been regarded as 0.2 mg, and this dose is used in the Republic of Korea and Japan, but in the United States and Europe, 0.4 mg is used for efficacy and safety. 7,26,27 With the approval by medical insurance, dose escalation of tamsulosin up to 0.4 mg is becoming popular in selected patients in Korea as well.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, the appropriate dose of tamsulosin has been regarded as 0.2 mg, and this dose is used in the Republic of Korea and Japan, but in the United States and Europe, 0.4 mg is used for efficacy and safety. 7,26,27 With the approval by medical insurance, dose escalation of tamsulosin up to 0.4 mg is becoming popular in selected patients in Korea as well.…”
Section: Discussionmentioning
confidence: 99%
“…13 The second subsequent RCT (61 men) compared terazosin against tamsulosin and found no significant difference in international prostate symptom score. 14 The third RCT comparing terazosin against alfuzosin also found no significant difference in the score. 15 Versus 5 reductase inhibitors: We found no systematic review.…”
Section: Benefitsmentioning
confidence: 98%
“…12 Versus each other: The first systematic review 9 identified three head to head comparisons that reported TURP versus less invasive surgical techniques clinical outcomes, and we found three subsequent RCTs of limited quality. [13][14][15] The largest RCT in the review (256 men) compared tamsulosin against alfuzosin. 12 The second RCT (103 men) compared alfuzosin against prazosin, and the third trial (98 men) compared tamsulosin against terazosin.…”
Section: Benefitsmentioning
confidence: 99%
“…A 6-week treatment phase was also employed in previous studies. They were able to observe the improvement of IPSS and Q max scores in a 6-week treatment phase or in an even shorter period (4 weeks) [24].…”
Section: Npgmentioning
confidence: 99%
“…ED was diagnosed according to IIEF when total of IIEF-EF domain scores were < 26 points. The scoring of the IIEF-EF domain allowed classification of each patient as having no (26-30), mild (17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (11)(12)(13)(14)(15)(16) or severe (1-10) ED. Adverse events were assessed at the end of the treatment course.…”
Section: Evaluation Proceduresmentioning
confidence: 99%